The Poetic Image in the Poets of the Diwan School - Hasan, Qultum Danqas; al-Basyir, Abdul Kafi Usman (Dzil Majaz: Journal of Arabic Literature, 2024)
This article entitled "Poetic Imagery Among Poets of the Diwan School" is a study of poetic imagery which means synonyms of forms of statement such as simile, metaphor, metonymy, and symbol, and is closely related to the sensory aspect. However, Colerogge combines the concept of image and says: It may be a scene or a copy of the sensible. The purpose of this article is to reveal the idea of ​​poetic imagery is based on the embodiment of psychological and emotional dimensions and other things that the poet wants to express with the meanings conveyed by the element of vitality. This article uses a qualitative approach with a library method. The results show that the idea of ​​poetic imagery is based on the embodiment of psychological and emotional dimensions and other things that the poet wants to express with the meanings conveyed by the element of vitality. For this reason, it is necessary to know the life of the poet in relation to the relationship from part to whole, so the researcher studies poetic imagery among several poets of the Diwan School, in the lines that are revealed. They are among the most prominent writers in the school. In creating their images, poets use inanimate and moving nature to form amazing interactions that predict movement, like living things. They also underestimated the importance of speech to the social environment and only mentioned a few